2022
DOI: 10.1177/02711214221075375
|View full text |Cite
|
Sign up to set email alerts
|

Initial Evaluation Practices to Identify Young Children’s Social Emotional Difficulties

Abstract: For young children with significant social emotional difficulties, early identification and intervention can mitigate later challenges. Early social emotional difficulties may indicate an early mental health condition, developmental delays, or educational disabilities. The Individuals with Disabilities Education Improvement Act (2004) includes provisions for finding and supporting young children with delays or disabilities associated with social emotional needs. Yet, few young children are identified and conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…One study in the state of Pennsylvania found that many young children were assessed in a private testing room, rather than a natural setting (Mattern, 2015). Stein & Steed (2022) reported that many early childhood professionals used clinic settings for initial evaluations during the COVID-19 pandemic. For some of these professionals, the clinic setting was a temporary adjustment due to health and safety concerns; however, some early childhood professionals indicated the use of clinic settings for EI and preschool special education initial evaluations in another study conducted prior to the pandemic (Steed & Stein, 2021).…”
Section: Natural Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study in the state of Pennsylvania found that many young children were assessed in a private testing room, rather than a natural setting (Mattern, 2015). Stein & Steed (2022) reported that many early childhood professionals used clinic settings for initial evaluations during the COVID-19 pandemic. For some of these professionals, the clinic setting was a temporary adjustment due to health and safety concerns; however, some early childhood professionals indicated the use of clinic settings for EI and preschool special education initial evaluations in another study conducted prior to the pandemic (Steed & Stein, 2021).…”
Section: Natural Settingsmentioning
confidence: 99%
“…In one study, Sullivan and colleagues (2019) found that many school psychologists made eligibility decisions that were not supported by the evaluation data. In Stein & Steed (2022) study, most early childhood professionals involved in determining eligibility for social emotional delays and disabilities in early intervention and preschool special education used their state's eligibility criteria; however, some expressed decision-making rules that conflicted with the state's eligibility guidelines. Further, when Barton et al, (2016) surveyed early childhood practitioners, they found large disparities across the state and school districts in the procedures, tools, and practices they used to identify young children with autism spectrum disorder.…”
Section: Eligibility Determination For Ei and Preschool Special Educa...mentioning
confidence: 99%